Agreement between frequency doubling perimetry and static perimetry in eyes with high tension glaucoma and normal tension glaucoma - Kogure, S (Copyright 2003 British Journal of Ophthalmology, 2003)
Aims: To investigate the agreement in results between frequency doubling technology (FDT) and the conventional automated static perimeter in eyes with normal tension glaucoma (NTG) and high tension glaucoma (HTG). Methods: 72 eyes of 36 patients, who had two or more experiences with the Humphrey field analyser (HFA) program C30-2, were examined with the screening C-20-1 program of FDT. The result of FDT at each of the 17 stimulus points was graded as one of four categories. 58 out of 76 test points of HFA were assigned to one of the 17 clusters corresponding to FDT test points. Each cluster was represented as the lowest (scotoma of HFA) or the highest (threshold of HFA) probability symbol of total deviation (TD) of the HFA test points included in the cluster. The agreement between scotoma/threshold of HFA and FDT results was evaluated for NTG and HTG. Results: In a total of 65 eyes, the Spearman coefficients between the FDT and HFA (threshold/scotoma of HFA) were 0.599 and 0.515 (p<0.0001), respectively. In the HFA mean deviation matched 20 HTG eyes and 20 NTG eyes, the number of points with abnormal FDT results were 102 and 62 in eyes with HTG and NTG, respectively. The eyes with HTG had more abnormal FDT results than NTG eyes (p=0.0014, Mann-Whitney U test). The kappa coefficient between FDT and threshold of HFA in eyes with HTG and NTG was 0.288 and 0.520, respectively, and the agreement between FDT and scotoma of HFA was 0.480 and 0.439, respectively. Conclusions: The best agreement of the results of FDT and HFA was observed in eyes with NTG using threshold of HFA. The eyes with HTG showed lower agreement with more abnormal points in FDT results, which suggests enough sensitivity of FDT in eyes with NTG, and higher sensitivity of FDT in eyes with HTG.